Luxury Vehicle Enthusiast: A Customer Loyalty Analysis in Jakarta - Amelia, Tifa Noer; Manungsong, Swastika Feranti; Jahja, Adi Susilo (Business Management Research, 2024)
This study aims to determine whether customer relationship management, public relations, and experiential marketing can affect customer loyalty. This study was conducted on luxury vehicle consumers in Jakarta. The study used a random sampling of 200 respondents. The research analysis technique is multiple linear regression using SPSS software. The results show that in both partial and simulant tests the model shows that customer relationship management, public relations, and experiential marketing effectively predict consumer loyalty. These findings show that the character of Jakarta as the capital city and the center of development in Indonesia impacts creating loyalty based on field assessment. About 50% of other variables need to be tested to strengthen factors that increase loyalty and show luxury vehicle enthusiasm in Jakarta. This research specifies an automotive distributor in Jakarta that specializes in luxury vehicles. Unlike the common vehicle customer, it is more manageable to maintain customer enthusiasm for luxury cars based on customer relationship management, public relations, and experiential marketing strategy.